Complications of Robotic Spine Surgery. (1st September 2019) - Myers, Daniel; Mao, Gordon; Yu, Alexander Kwong-Tak; Whiting, Donald M
Abstract: INTRODUCTION: Robotic assisted spine surgery is becoming increasingly widespread during spinal instrumentation cases. We report our early experience utilizing robotic assisted spinal instrumentation. The aim of the study is to review complications experienced during robotic assisted spinal instrumentation including analysis of pedicle screw accuracy, medical, and surgical complications. METHODS: This study was performed as a descriptive, retrospective study. We reviewed cases over the course of 12 mo and examined all operative and postoperative data including pedicle screw accuracy, medical, and surgical complications related to the surgery and hospital stay. Pedicle screw accuracy was assessed utilizing the Gertzbein–Robbins scale. RESULTS: The study included 67 consecutive patients undergoing 68 robotic-assisted procedures. Patient ages ranged from 20 to 90 yr. There were 37 males and 30 females. Indications for surgery included degenerative disease 33, trauma 24, tumor 5, and infection 1. There were a total of 592 pedicle screws placed. A total of 26 (4.3%) screws were revised intraoperatively using the robot. An additional 32 (5.4%) screws were aborted from robotic assistance. Pedicle screw accuracy was noted to be excellent with 97% of screws rated as clinically acceptable. There were 4 deaths (5.8%), 18 patients (26%) experienced a medical complication, 26 patients (38%) experienced a surgical complication and 6 patients (9%) experienced both a medical and surgical complication. A total of 38 patients (55%) experienced any morbidity or mortality related to surgery. Mean operative time was 277 min. CONCLUSION: We report our initial experience with robotic-assisted spine surgery. Pedicle screw accuracy was noted to be high. We experienced a broad array of medical and surgical complications. The high complication rate may be due to long operative times and presence of a learning curve utilizing the robot. Further study is warranted to note if more experience decreases complication rates. It is unclear if the complication rate is significantly different compared to traditional methods of spinal instrumentation.